Young males' perspectives on pregnancy, fatherhood and condom use: Where does responsibility for birth control lie? - Smith, Jennifer; Fenwick, Jennifer; Skinner, R.; Merriman, Gareth; Hallett, Jonathan (Elesvier, 2011)
Background: To improve our understanding of males’ role in contraceptive practices, this paper explores the relationship between young males’ perspectives on pregnancy and fatherhood and their attitudes, beliefs and practices in relation to condom use and birth control. Methods: Semi-structured interviews were conducted with a sample of 42 males aged 15–25 years. A systematic process of thematic analysis was used to reduce and organise the narrative data around the focus areas of relationships, sex, condom use, STIs and pregnancy/fatherhood. To facilitate the emergence of key patterns in the data, new data was constantly compared with existing ideas to formulate and refine codes and descriptive categories. Results: The analysis revealed a clear discrepancy between young males’ desire to prevent pregnancy and the level of control they assumed over this. Despite pregnancy emerging as the overriding concern for participants, this failed to motivate continued use of condoms when STI risk was perceived as low and a partner was using birth control. Reliance on a partner’s use of hormonal contraceptives and in several cases, beliefs of low personal responsibility for pregnancy prevention reduced young males’ participation in fertility control. Conclusions: Young males’ unfavourable attitudes toward immediate pregnancy and fatherhood provide a unique opportunity for safe sex promotion by encouraging greater ownership over sexual and reproductive health outcomes. However, this requires a shift in the meanings associated with condoms, from a disease prevention only orientation to one that promotes condom use as a positive act for self and partner protection.